E0021 A novel approach of proteomics to study the mechanism of action of grape seed proanthocyanidin extracts on aortic arteriosclerosis in diabetic rats. (17th November 2010) - Bao-Ying, Li; Xiao-Li, Li; Hai-Qing, Gao; Mei, Cheng; Ling, Xu; Xian-Hua, Li
Abstract : Objective: Diabetic macrovascular complications are the leading cause of mortality in diabetic patients. To prevent the development of this disease and to improve advanced arteriosclerosis, effective therapies directed towards the key molecular target are required. Grape seed proanthocyanidin extracts (GSPE) have been reported to be effective in treating arteriosclerosis, while little is known about the functional protein changes. Methods: We used streptozotocin to induce diabetic rats. GSPE (250 mg/kg body weight/day) were administrated to diabetic rats for 24 weeks. Serum glycated haemoglobin and advanced glycation end products (AGEs) were determined. Electronic microscope was used to observe the changes of aortic ultrastructure. Immunohistochemistry was used to evaluate the receptor of advanced glycation end products (RAGE) protein expression in aortic tissue. Consequently, 2-D difference gel electrophoresis and AutoFlex martix-assisted laser desorption/ionization time-of-flight mass spectrometry with LIFT technology or liquid chromatography electrospray ionisation mass spectrometry/mass spectrometry were used to investigate aortic protein profiles among the control, untreated, and GSPE treated diabetic rats. Results: GSPE significantly decreased aortic PWV, blood pressures, aortic medial thickness (p<0.05), and inhibited the migration of vascular smooth muscle cells. GSPE significantly reduced the AGEs (p<0.05), and the expression of RAGE in aorta of diabetic rats. The expression of 23 proteins was found either up-regulated or down-regulated in the aorta of untreated diabetic rats. Only the expression of 15 proteins was found either down-regulated or up-regulated in the aorta of GSPE treated diabetic rats. Among these proteins, in comparison with the aortic tissue of diabetic rats, the differential proteomic analysis of the aortic tissue of diabetic rats, treated by GSPE further revealed the variation of fifteen proteins, namely, lamin A, ATP synthase alpha chain, proline arginine-rich end leucine-rich repeat protein precursor, LOC500183 protein, heat Shock Protein 27, enoyl-CoA hydratase, glutamate dehydrogenase, protein-L-isoaspartate (D-aspartate) O-methyltransferase 1, lactadherin, leucine aminopeptidase 3, adenylyl cyclase- associated protein 1, apolipoprotein A-I, catalase, Dermcidin, and fibrinogen β chain. In brief, the differentially expressed proteins were related to many important biological functions including metabolism, oxidative stress, signal transduction, cell proliferation, cell growth, apoptosis and heat shock. Conclusion: GSPE plays an important role against diabetic macrovascular complications. Our findings might help to better understanding of the mechanism of diabetic macrovascular complications, and provide novel targets for estimating the effects of GSPE therapy.